Strong electronic coupling dominates the absorption and fluorescence spectra of covalently bound BisBODIPYs - Knippenberg, Stefan; Bohnwagner, Mercedes V.; Harbach, Philipp H. P.; Dreuw, Andreas (The journal of physical chemistry. A, Molecules, clusters, and aerosols, 2015)
The absorption spectrum of a representative BisBODIPY molecule is investigated using high-level quantum chemical methodology; the results are compared with experimental data. The S1 and S2 excited states are examined in detail to illuminate and to understand the electronic coupling between them. With the help of model systems in which the distance between the BODIPY monomers is increased or in which the dihedral angle between the subunits is changed, the electronic coupling is quantified, and its influence on energetics and oscillator strengths is highlighted. For the explanation of the experimental spectrum, orbital interaction effects are found to be important. Because of the large experimental Stokes shift of BisBODIPY, the nature of the emissive state is investigated and found to remain C2 symmetric as the ground state, and no localization of the excitation on one BODIPY subunit occurs. The excitonic coupling is in BisBODIPY still larger than the geometry relaxation energy, which explains the absence of a pseudo-Jahn-Teller effect.